Study of Indonesia's international macroeconomic indicators before and during the covid-19 pandemic - Dewi Mahrani Rangkuty; Bakhtiar Efendi; Lia Nazliana Nasution (Jurnal Riset Pendidikan Ekonomi, 2021)
This study aims to review Indonesia's macroeconomic indicators before and during the covid-19 pandemic. Using time-series data sourced from ceicdata, this study uses non-parametric statistical methods of different tests (sign tests). The results showed that there is a significant difference between before and during the covid-19 pandemic on international macroeconomic indicators of the rupiah exchange rate against USD, external debt, reserves, and Indonesian CPI. Recommended to the Government of Indonesia through Bank Indonesia and other relevant Ministries need a strict policy on a rupiah exchange rate that leads to price stability to reduce the rate of inflation, management and disclosure of external debt information, the achievement of trade balance surplus to increase reserves towards increasing domestic economic growth.